Amino Acid δ15N Can Detect Diet Effects on Pollution Risks for Yellow-Legged Gulls Overlooked by Trophic Position - Bode, Antonio; Besada, Victoria; Pérez-Fernández, Begoña; Viñas, Lucía (Frontiers in Marine Science, 2021)
The use of top-consumers as bioindicators of the health of food webs is hampered by uncertainties on their effective use of resources. In this study, the abundance of stable nitrogen isotopes in amino acids from homogenized eggs of the Yellow-legged Gull (Larus michahellis) allowed to identify variations in trophic resource exploitation between geographically adjacent nesting colonies in the Ria de Vigo (NW Spain) that exhibited marked differences in pollutants. Eggs from nests in the Cíes Islands (located in a National Park) showed a large variability in stable carbon and nitrogen isotopes in bulk egg content encompassing that of eggs from Vigo city (a major fishing harbour). However, both colonies differed in the relative concentration and abundance of nitrogen isotopes of lysine, an essential amino acid present in marine prey but also extensively used in feed stocks for poultry and swine. Notwithstanding the similarity in trophic position for both colonies, gulls from Cíes Islands may have acquired a substantial fraction of lysine from garbage dump sites while those from the urban colony relied on fish discards. This unexpected conclusion is partly supported by the large variability reported for gulls diet in this region and calls for detailed estimations of diet when assessing the conservation status and pollution risks of marine ecosystems.